Aligning enterprise, system, and software architectures - Mistrík, Ivan. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2013)
"This book covers both theoretical approaches and practical solutions in the processes for aligning enterprise, systems, and software architectures"--Provided by publisher.